Desain dan Kasus Pembajakan Karya Intelektual di Indonesia - Ferry Darmawan; Saefuddin Saefuddin (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2005)
Design piracy, though considered as serious problems, is often overlooked. This phenomenoncommonly found in Third World countries. The government have been have been employing many ways to reduce piracy, such as adopting Intellectual Property Rights. But the effort to combat piracy was challenged by some parties which benefited from such activities. Piracy, in micro perspective, eliminates fair competition and creates unfair competition. The culture of piracy also harassed and submerged the role of law. Law enforcement toward Intellectual Property Rights is a must. The challenge is how to awaken members of society toward the importance of Intellectual Property Rights.